DOI: 10.11606/d.22.2013.tde-26092013-163522
|View full text |Cite
|
Sign up to set email alerts
|

A interação estudante - tecnologia educacional digital em enfermagem neonatal

Abstract: Castro, Fernanda Salim Ferreira de. The interaction student-digital education technology in neonatal nursing. Ribeirão Preto, 2013 102 p. Dissertation ou Thesis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
6

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
0
2
0
6
Order By: Relevance
“…The relevance of this instrument is due to the fact that, currently, there are technologies that use the most diverse means to integrate and facilitate learning, care with the patient and the communication of the professional with the team members and with the institution. (17) Using ICTs can be considered a paradigm of innovation and evolution of societies. Nonetheless, more important than any technology is how people use it in their individual or collective development, i.e., how people make technologies be useful in their lives given that their learning styles must occur in a way comfortable to users, avoiding resistance to their use.…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of this instrument is due to the fact that, currently, there are technologies that use the most diverse means to integrate and facilitate learning, care with the patient and the communication of the professional with the team members and with the institution. (17) Using ICTs can be considered a paradigm of innovation and evolution of societies. Nonetheless, more important than any technology is how people use it in their individual or collective development, i.e., how people make technologies be useful in their lives given that their learning styles must occur in a way comfortable to users, avoiding resistance to their use.…”
Section: Discussionmentioning
confidence: 99%
“…Possuem o papel de permitir a interação e comunicação entre pessoas de diversos países, culturas e crenças, favorecendo as relações sociais e a busca por informações que são facilmente localizadas. Essa fonte tão diversificada torna-se muito importante no campo do conhecimento, pois promove modificações no processo de aprendizagem, abrindo caminhos para novas oportunidades e desafios para educadores e estudantes (SILVA; PEDRO; COGO, 2011; COSTA et al, 2011; BOTTI; CARNEIRO; PEREIRALL, 2011; HOLANDA et al, GÓES et al, 2015;LEITE et al, 2013;FONSECA et al, 2015;CASTRO et al, 2015).…”
Section: Teleduc (Módulo Educativo)unclassified
“…Por se tratar de um objeto facilitador e auxiliador do processo de aprendizagem, GÓES et al, 2015;FONSECA et al, 2015;CASTRO et al, 2015).…”
Section: Teleduc (Módulo Educativo)unclassified
“…Studies that evaluated educational technologies demonstrated that their interfaces provided a pleasant and motivating study environment. Tools (sounds, images and texts) were used to simulate the reality of a work environment, as well as allowed the access to information in a quick and secure manner (18) .…”
Section: Didactic and Pedagogical Toolsmentioning
confidence: 99%